Long Range (LoRa) Network Planning Analysis at 920-923 MHz Frequency for Region Palabuhanratu - Delisya Nabilla Hendrawan; Uke Kurniawan Usman; Budi Prasetya (Universitas Respati Yogyakarta, 2022)
LoRa technology in Indonesia is currently in the development stage to accelerate the digitalization of cheap and reliable connectivity-based smart utilities. Palabuhanratu is a potential area for LoRa network infrastructure development due to the density of end devices in Palabuhanratu which causes the process of sending data on a network to be hampered. The parameters used in the LPWA software simulation include Signal Level, Noise to Interference Carrier Level and Link Budget. This research method analyzes the simulation results on Signal Level, Noise to Interference Carrier Level and Link Budget as parameters for the construction of LoRa network infrastructure at a frequency of 920-923 MHz in Palabuhanratu. The research is divided into two planning stages. The first planning stage is the calculation of capacity and calculation of coverage. The second planning stage is simulation using Atoll Low Power Wide Area software. The results of the simulation analysis obtained in this study are that there are 10 gateway capacities using the Atoll application software. The average values generated by the simulation parameters include the Signal Level, which is -64.06 dBm with the ”good” category based on the KPI standard, which is more than - 80 dBm and the Noise to Interference Carrier Level parameter of 27.71 dB which is included in the ”excellent” category, namely greater than 12 dBm in KPI standardization, and the resulting path loss is -107.74 dBm at a cell radius of 1.261 km.